Heterogeneous Effects of Monetary Policy on Industries: Evidence from Publicly Traded Firms in Peru - Chavez, Carlos (Latin American Journal of Trade Policy, 2023)
This paper studies the effects of a monetary policy shock on the industry’s profitability through publicly traded firms in Peru. I use a monetary policy shock that controls the possible endogeneity between the monetary policy with the economic activity and the Central Bank’s anticipation of economic events. I use two profitability measures: ROA and Net Profits. The methodology is Local Projections (LP) because it allows for control of the persistence of monetary policy shocks; in case of biases, it is usually smaller than the traditional methodologies used, such as vector autoregressive (VAR), and because Local Projection is parsimonious. The results I find are heterogeneous and differentiated in terms of quantification and persistence for those dependent variables through industries. These results suggest the existence of a strong credit channel in the transmission mechanism of a monetary policy shock.